W. Proctor Harvey: A Master Clinician-Teacher's Influence on the History of Cardiovascular Medicine - March, S. Kimara (2002)
Medicine has become driven by research and technology, both of which have yielded indisputable benefits. Yet we are now so dependent upon such advancements that many practitioners have lost the basic clinical skills that enable bedside diagnosis. In the 2nd half of the 20th century, W. Proctor Harvey helped to keep alive the classic art of medicine. (Tex Heart Inst J 2002;29:182–92)